2020
DOI: 10.3390/f11030264
|View full text |Cite
|
Sign up to set email alerts
|

First Age-Estimation Model for Dracaena ombet and Dracaena draco subsp. caboverdeana

Abstract: Research Highlights: The first model for crown age estimation was developed for Dracaena ombet Heuglin ex Kotschy and Peyr. and D. draco subsp. caboverdeana Marrero Rodr. and R. Almeida. Background and Objectives: Dracaena species are monocotyledon trees without annual tree rings. Most arborescent dragon tree species are endangered; thus, it is important to determine the age structures of these populations for proper conservation management strategies, and for modelling of population trends. For these reasons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Our classification of the seedling stage corresponds with the juvenile and partly with the medium juvenile stages of the classification used in studies of D. cinnabari (Maděra et al, 2020). Growth rate of dragon trees is still poorly known, but based on available growth rates (Adolt and Pavlis, 2004;Lengálová et al, 2020;Maděra et al, 2020), we assume saplings can be up to c. 25 years.…”
Section: Field Workmentioning
confidence: 99%
“…Our classification of the seedling stage corresponds with the juvenile and partly with the medium juvenile stages of the classification used in studies of D. cinnabari (Maděra et al, 2020). Growth rate of dragon trees is still poorly known, but based on available growth rates (Adolt and Pavlis, 2004;Lengálová et al, 2020;Maděra et al, 2020), we assume saplings can be up to c. 25 years.…”
Section: Field Workmentioning
confidence: 99%
“…According to previous research, the juvenile stages of D. cinnabari from seedling to first flowering can take 200–250 years or even more ( Maděra et al., 2018 ), thus demonstrating that this species takes an extremely long time to grow and mature. Owing to difficulties related to investigating natural population aging, several methodologies have been developed for age estimation in such trees ( Adolt and Pavliš, 2004 ; Adolt et al., 2012 ; Jura-Morawiec, 2019 ; Lengálová et al., 2020 ). These methods have all demonstrated that the dragon tree is a long-lived species.…”
Section: Introductionmentioning
confidence: 99%
“…According to the research of Maděra (2018), the juvenile stages of D. cinnabari from seedling to the first flowering will take about 200-250 years, even more (Maděra et al ., 2018), demonstrating it is an extremely slowly growth and slowly maturing species. Due to the difficulties in the authentic study of natural population aging, several methodologies of age estimation were developed and improved (Adolt & Pavliš, 2004; Adolt et al ., 2012; Jura Morawiec, 2019; Lengálová et al ., 2020). Anyway, they all showed that the dragon tree is a long-lived species.…”
Section: Introductionmentioning
confidence: 99%